Constrained Peptides with Fine‐Tuned Flexibility Inhibit NF‐Y Transcription Factor Assembly. (17th October 2019) - Jeganathan, Sadasivam; Wendt, Mathias; Kiehstaller, Sebastian; Brancaccio, Diego; Kuepper, Arne; Pospiech, Nicole; Carotenuto, Alfonso; Novellino, Ettore; Hennig, Sven; Grossmann, Tom N.
Abstract: Protein complex formation depends on the interplay between preorganization and flexibility of the binding epitopes involved. The design of epitope mimetics typically focuses on stabilizing a particular bioactive conformation, often without considering conformational dynamics, which limits the potential of peptidomimetics against challenging targets such as transcription factors. We developed a peptide‐derived inhibitor of the NF‐Y transcription factor by first constraining the conformation of an epitope through hydrocarbon stapling and then fine‐tuning its flexibility. In the initial set of constrained peptides, a single non‐interacting α‐methyl group was observed to have a detrimental effect on complex stability. Biophysical characterization revealed how this methyl group affects the conformation of the peptide in its bound state. Adaption of the methylation pattern resulted in a peptide that inhibits transcription factor assembly and subsequent recruitment to the target DNA. Abstract : Ein Peptid‐abgeleiteter Inhibitor des NF‐Y‐Transkriptionsfaktors wurde entwickelt, indem zuerst die Konformation eines Peptidepitops durch Kohlenwasserstoff‐Klammerung eingeschränkt und anschließend dessen Flexibilität eingestellt wurde. In den resultierenden Peptiden wirkt sich eine nicht wechselwirkende α‐Methylgruppe negativ auf die Komplexstabilität aus. Das entsprechende demethylierte Peptid inhibiert die Assemblierung des Transkriptionsfaktors und dessen nachfolgende Bindung an DNA.